The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/vnl.21858
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of talc/calcined kaolin binary fillers on rigid PVC: Improved properties of PVC composites

Abstract: This study aims to develop poly(vinyl chloride) (PVC) composites prepared by melt mixing by using a combination of talc and calcined kaolin as filler in order to improve the disadvantages of rigid PVC, which is widely used in industry, such as poor mechanical properties and low thermal stability. In addition, PVC/talc and PVC/calcined kaolin composites were also examined for comparison. The calcined kaolin is modified with urea to increase the surface area (chemical treatment), while the surface of both filler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Polyvinyl chloride (PVC) is one of the high‐strength thermoplastic polymers with paramount chemical stability, durability, formulating versatility, corrosion resistance, and cost‐effectiveness that make them potent candidates for automotive, construction and electronic applications such as flooring, bottles, pipes, indwelling catheters, fittings, and food packing. [ 1–4 ] Since PVC is more flexible and resistant to moisture than vulcanized rubber, it may effectively replace the latter. [ 5 ] However, their uses are restricted due to their poor mechanical properties, low stiffness, and instability to heat and light.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Polyvinyl chloride (PVC) is one of the high‐strength thermoplastic polymers with paramount chemical stability, durability, formulating versatility, corrosion resistance, and cost‐effectiveness that make them potent candidates for automotive, construction and electronic applications such as flooring, bottles, pipes, indwelling catheters, fittings, and food packing. [ 1–4 ] Since PVC is more flexible and resistant to moisture than vulcanized rubber, it may effectively replace the latter. [ 5 ] However, their uses are restricted due to their poor mechanical properties, low stiffness, and instability to heat and light.…”
Section: Introductionmentioning
confidence: 99%
“…These properties are improved by combining PVC with various fillers, plasticizers, and stabilizers. [ 1,6 ] Shi et al reported the impact of plasticizer concentration and molecular structure on the flexural fatigue of soft PVC. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations